2008
DOI: 10.1111/j.1742-6723.2008.01068.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of morphine use and time to initial analgesia in an Australian emergency department

Abstract: T-A is an important indicator of the quality of ED services. Severity of illness and patient volume were significant factors associated with extended T-A. Strategies for improving pain management in the complex ED environment are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 22 publications
1
16
0
Order By: Relevance
“…Our data are similar to findings from several recent studies that found patients who received a low priority triage score experienced longer delays to administration of analgesics 2, 3, 5 . In the context of crowding, assignment of a lower priority triage level has a great impact on delays to care for all patients.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Our data are similar to findings from several recent studies that found patients who received a low priority triage score experienced longer delays to administration of analgesics 2, 3, 5 . In the context of crowding, assignment of a lower priority triage level has a great impact on delays to care for all patients.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies have also found patients with RC experience more rapid treatment when compared with all ED patients who received morphine sulfate for treatment of acute pain. 5 Delays associated with arrival shift may reflect crowding, however, regardless of arrival time, we found delays were still consistently longer for patients with SCD. Patients arriving during the night shift experienced the shortest time to receiving an initial analgesic; this is a variable that cannot be controlled.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations